Water Contaminated with Didymosphenia Geminata Generates Changes in Salmo Salar Spermatozoa Activation Times - Peredo-Parada, M (Elsevier, 2015)
Didimosphenia geminata ("didymo"), has become a powerful and devastating river plague in Chile. A system was developed in D. geminata channels with the purpose evaluating the effects of water polluted with didymo on the activation of Atlantic salmon (. Salmo salar) spermatozoa. Results indicate that semen, when activated with uncontaminated river water had an average time of 60. ±. 21. s. When using Powermilt, (a commercial activator), times of 240. ±. 21. s are achieved, while rivers contaminated with D. geminata achieve a motility time of 30. ±. 12. s. Interestingly enough, the kinetic parameters of VSL, VCL and VAP showed no significant changes under all of the conditions. Furthermore, the presence of D. geminata reduces activation time of the samples as the cells age, indicating increased effects in spermatozoa that are conserved for more than 5 days. D. geminata has antioxidant content, represented by polyphenols; 200. ppm of polyphenol were obtained in this study per 10. g of microalgae. Spermatozoa exposed to these extracts showed a reduction in mobility time in a dose dependent manner, showing an IC50 of 15. ppm. The results suggest an effect on spermatozoa activation, possibly due to the release of polyphenols present in contaminated rivers, facilitating the alteration of sperm motility times, without affecting the viability or kinetics of the cells. These findings have important implications for current policy regarding the control of the algae. Current control measures focus on the number of visible species, and not on the compounds that they release, which this study shows, also have a problematic effect on salmon production. © 2015 Elsevier B.V.